Trading Nokia: the roles of the Helsinki vs the New York stock exchanges - Esa Jokivuolle; Markku Lanne (Bank of Finland, 2004)
We use the Autoregressive Conditional Duration (ACD) framework of Engle and Russell (1998) to study the effect of trading volume on price duration (ie the time lapse between consecutive price changes) of a stock listed both in the domestic and the foreign market.As a case study we use the example of Nokia's share, which is actively traded both in the Helsinki Stock Exchange and the New York Stock Exchange (NYSE).We find asymmetry in the volume-price duration relationship between the two markets.In the NYSE the negative relationship is much stronger and exists both during and outside common trading hours.Outside common trading hours no such relationship is significant in Helsinki.Based on the theory of Easley and O'Hara (1992), these results could be interpreted in that informed investors in Nokia mainly trade in the US market whereas Helsinki is the more liquidity-oriented trading place.
URN:NBN:fi:bof-20140807642
Keywords: G14; G19; 330; cross-listing; Autoregressive Conditional Duration; market microstructure